2008
DOI: 10.1016/j.biopsycho.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural phenotypes of common and rare genetic variants

Abstract: Neuroimaging methods offer a powerful way to bridge the gaps between genes, neurobiology and behavior. Such investigations may be further empowered by complementary strategies involving chromosomal abnormalities associated with particular neurobehavioral phenotypes, which can help to localize causative genes and better understand the genetics of complex traits in the general population. Here we review the evidence from studies using these convergent approaches to investigate genetic influences on brain structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 206 publications
(171 reference statements)
0
9
0
Order By: Relevance
“…[38][39][40][41] More recent studies have demonstrated additional rare variant influences on the pathogenesis of a variety of complex diseases and traits such as type 1 diabetes, colorectal cancer, plasma lipoprotein levels and neurological disorders. [42][43][44][45][46][47][48][49] Screening candidate genes in groups of patients for germline variation is the first step in unraveling rare variation, a step that is already being made much easier by the increasing accessibility of nextgeneration sequencing technologies. However, functional studies of the most interesting variants must follow closely.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] More recent studies have demonstrated additional rare variant influences on the pathogenesis of a variety of complex diseases and traits such as type 1 diabetes, colorectal cancer, plasma lipoprotein levels and neurological disorders. [42][43][44][45][46][47][48][49] Screening candidate genes in groups of patients for germline variation is the first step in unraveling rare variation, a step that is already being made much easier by the increasing accessibility of nextgeneration sequencing technologies. However, functional studies of the most interesting variants must follow closely.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the quality of the data, any MRS spectrum with NAAlinewidth of >8 Hz or (NAA level/residue) b7 was excluded from the analysis (Bearden et al, 2008;Singh et al, 2009), on which basis 11 pairs of twins were excluded. To calculate the metabolite ratios, the measures of NAA, Cr, Cho and ml were normalized with the water peak in any individual.…”
Section: Mrs Data Analysismentioning
confidence: 99%
“…Moreover, schizophrenia patients with 22qDS have clinical profiles that are indistinguishable from schizophrenia patients without the deletion (Bassett et al, 2003; Murphy et al, 1999). Well-defined genetic subtypes of neuropsychiatric disorders like 22qDS – with a known, homogeneous etiology – may be informative for developing and understanding the pathophysiology of schizophrenia in the broader population (Bearden et al, 2008). However, there is wide variability in the phenotype associated with 22qDS, and it is not known why only a certain percentage of individuals with the microdeletion develop psychosis.…”
Section: Introductionmentioning
confidence: 99%